Análise das equações de Navier-Stokes no escoamento bidimensional em dutos com formulação em variáveis primitivas via GITT - Andrade, Juanice Helena de (2010)
In this paper the Generalized Integral Transform Technique is employed to produce hybrid solutions for the velocity and pressure fields of a newtonian fluid in two dimensional flow. The problem is formulated by using primitive variables and the necessary mathematical manipulations were used to obtain the Poisson equation for the pressure field. The momentum equations in the axial direction of flow and Poisson are transformed to remove the transversal dependency. The resulting transformed fields are solved with the IMSL numerical subroutine, DBVPFD. The obtained results for the longitudinal velocity profile at the center of the channel are compared with the available data in the open literature for validation and model fitting. Even so, studies are carried out about the convergence of the solution for the velocity profile in the centerline as well as testing different values of the scale factor of axial coordinate for the choice of a factor which can fit perfectly for comparison with available data. Interest practical datas such as: friction factor and mean velocity are obtained along the duct for a entry condition into the parallel flow channel (v = 0).